Application of spin echoes in the regime of weak dephasing to T1‐mapping of the lung. Issue 2 (17th April 2017) - Assländer, Jakob; Glaser, Steffen J.; Hennig, Jürgen
Abstract : Purpose: This work presents an approach to mapping the entire lung's proton density and T 1 within a single breath‐hold and analyzes the apparent T 1 when exciting with a spin echo generating pulse in comparison to a standard gradient echo acquisition. Methods: An inversion‐recovery SNAPSHOT‐FLASH sequence with a stack‐of‐stars k‐space readout with a golden angle increment was modified to use a spin echo generating radiofrequency‐pulse for excitation. Data of five volunteers were acquired on a 3T scanner and image reconstruction was performed by an iterative algorithm adopted from MR‐Fingerprinting. Results: The feasibility of acquiring quantitative maps of the entire lung with a resolution of 5 × 5 × 10 mm within 7.5 s is demonstrated. It is shown that the proposed spin echo forming radiofrequency‐pulse increases the apparent proton density compared to a rectangular pulse. Further, the apparent T 1 is reduced in the spin echo case compared to the gradient echo sequence. Conclusion: The proposed spin echo based method results in T 1 maps that are comparable to the ones that were acquired with ultra‐short echo time sequences elsewhere. The T 1 shortening is believed to originate from increased signal contributions of the extra vascular compartment, which has a short T 2 ∗ and T 1 . Magn Reson Med 79:960–967, 2018. © 2017 International Society for Magnetic Resonance in Medicine.